Perinatal Stroke; Risk Factors and Outcome. A Study from Aga Khan University Hospital Karachi - Baloch, Fozia; Abro, Falak; Khalid, Qurat-Ul-Ain; Chand, Prem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency, risk factors and the outcomes of a perinatal stroke.Study Design: Cross-sectional study.Place and Duration of Study: Neonatal Intensive Care Unit, Department of Pediatrics, Aga Khan University Hospital, Karachi Pakistan, from Jan to Dec 2019.Methodology: Neonates with perinatal stroke confirmed on the neuroimaging, were included in the study. The primary outcomes were risk factors, divided into 3 groups, maternal, placental and neonatal. The secondary outcome was the condition at the time of the discharge.Results: A total of 58 patients were included in the study. Maternal risk factors identified in the study, were intrauterine infections 10 (17.2%), anti-phospholipid syndrome, gestational diabetes 8 (13.8%) and preeclampsia 7 (12.1%). Chorioamnionitis 9 (15.5%), antepartum hemorrhage 6 (10.3%), and placenta previa 4 (6.9%) were the placental risk factors. Neonatal risk factors were birth asphyxia 35 (60.3%), sepsis/meningitis 8 (13.8%), premature birth 6 (10.3%) and fetal bradycardia 4 (6.9%). Resuscitation was needed in 35 (60.3%) neonates with birth asphyxia. Haemorrhagic stroke was observed in 38 (65.5%) cases, ischemic stroke in 14 (24.1%) cases and mixed type of stroke was found in 6 (10.3%) patients. The total mortality rate in our study was13.8%.Conclusion: Haemorrhagic stroke was more common than ischemic or mixed stroke among the patients of perinatal stroke at our healthcare facility. Patients with low APGAR score at 5 minutes, birth asphyxia and male gender, were most affected.